On the problem of calculating shear deformations in prismatic bars made of polymer materials under tension with torsion - Резнік, В. С.; Ушаков, О. В.; Горун, О. Ю. (Київський національний університет імені Тараса Шевченка, 2021)
The process of creep of prismatic rods made of linear-viscoelastic polymeric materials under combined loading is considered. Defining equations that determine the relationship between strains, stresses and time are given in the form of a superposition of shear and bulk strain. The object of study is prismatic bars made of fiberglass ST-1. The area of linearity of the model is substantiated on the basis of the hypothesis of the existence of the creep function, which is built on the yield curves, a single diagram of long-term deformation and the statistical value of the quantile of statistics. The region of linear-elastic deformation is recognized based on the fulfillment of the condition of existence of a single creep function. The defining equations of the model contain a set of functions and coefficients determined from the basic experiments. On the basis of the relations between the kernels of the one-dimensional stress state, the parameters of the kernels under the condition of a complex stress state are determined. The linearity of viscoelastic properties is given by the Boltzmann-Voltaire equations. The fractional-exponential kernels of heredity are chosen as the kernels of heredity. The obtained values of the core parameters are used to calculate the creep deformations of prismatic bars made of ST-1 fiberglass under conditions of simultaneous tensile tension. Pages of the article in the issue: 115 - 118 Language of the article: Ukrainian
Keywords: linear viscosity; longitudinal creep; shear creep; volume creep; heredity nuclei; isochronous diagrams; quantile of statistics; лінійна в'язкопружність; складний напружений стан; повздовжня повзучість; зсувна повзучість; об’ємна повзучість; ядра спадковості; квантиль статистики